THE EFFECT OF CHAOS THEORY ON THE PREDICTABILITY OF THE ATMOSPHERE - Aydoğmuş, Fatma; Tosyalı, Eren (Bilal GÜMÜŞ, 2017)
It is known that atmosphere is a dynamical system that constantly changing and moving. It is a very difficult problem to completely determine and explain the change in the atmosphere. But the mathematical models can help us to understand and explain the dynamical processes in the atmosphere. Examination of the movements of the atmosphere is one of the most exciting applications of chaos theory. The main goals of this presentation will be try to discuss the effect of chaos theory on the predictability of the atmosphere. For this purpose, we focus on one of the most specific examples of atmosphere events, is global climate change.
Keywords: atmosphere; chaos; autonomous